If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 6x Solving 18 = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 18 + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 18 + -6x = 0 Add '-18' to each side of the equation. 18 + -18 + -6x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -6x = 0 + -18 -6x = 0 + -18 Combine like terms: 0 + -18 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| 9y-7(x-y)-x= | | N^2-3+2=0 | | 13x+6-3=12x-3 | | 4(9b+c-5a)-5(a-3c+4b)= | | 33=(3x-8)(7x+4) | | 7(p+7q-13)= | | N^2-13n+40=0 | | 5(6y+12)=6(12y-4) | | 30=-1.2v | | 2x^2+10x-18=0 | | 5(6y+12)=6(12-4) | | -2(4n+4)=2 | | 15x^4-12x^3+3x^2=0 | | y-(-3)=2(x-2) | | (-1)x^3=27 | | 6x+2.72=4.22 | | (1+z)(5z-2)=0 | | 10x+26(x-2)=128 | | 5x+27(x-4)=84 | | 3m+38=9m-4 | | 5m+14=9m-2 | | -6z+2(5-3z)=8(-3z+2)+10 | | 4(p+8q-13)= | | 22-2=6n | | -3k=14-k | | 6y-8(-3)=24 | | 6y-8x=24 | | 5(x+3)=3(7x+3)-2 | | g(x+5)=x^2+2x+3 | | 4x^2+8-77=00 | | 6x+21=2x-1 | | g(-1)=x^2+2x+3 |